FORMULATION AND EVALUATION OF PULSATILE DRUG DELIVERY SYSTEM FOR NOCTURNAL ASTHMA USING FICUS RELIGIOSA - Samruddhi Uday Padhye; Apeksha Chandrakant Rahate; Madan Dadaso Pomaje (The Bioscan, 2025)
Up to 75% of asthmatics experience nocturnal asthma, marked by early morning flare-ups due to increased bronchoconstriction and airway inflammation. Conventional continuous-release medications often fail to provide optimal control during these critical hours. This study aims to develop a Chronomodulated Pulsatile Drug Delivery System (PDDS) using the Pulsincap platform for targeted drug release in sync with circadian rhythms. The system incorporates Ficus religiosa (peepal tree) extracts, known for their anti-inflammatory properties, particularly due to their quercetin content, offering a natural therapeutic approach with minimal side effects.The PDDS features a hydrogel plug to ensure delayed drug release, timed to coincide with peak asthma symptoms. The formulation was optimized through ex vivo pharmacological assessments, stability tests, and in vitro drug release studies, demonstrating effective and consistent drug release at the desired time. The results revealed significant anti-asthmatic potential, stable performance under various conditions, and enhanced symptom control. By combining chronotherapy with herbal medicine, this system improves asthma management by reducing side effects and boosting patient adherence. Moreover, the PDDS platform offers broader potential for treating other circadian-related conditions like rheumatoid arthritis and hypertension, paving the way for tailored, time-specific therapies with improved clinical outcomes.